Effects of Rosmarinus officinalis essential oil on germ tube formation by Candida albicans isolated from denture wearers - Gauch, Lurdete Maria Rocha (2014)
Introduction: The aim of this study was to investigate the effects of Rosmarinus offi cinalis essential oil on germ tube formation by Candida albicans isolated from denture wearers. Methods: Ten C. albicans isolates recovered from denture wearers were tested using 10% fetal bovine serum with or without 4% R. offi cinalis essential oil. Results: The essential oil from R. offi cinalis completely inhibited germ tube formation in the investigated C. albicans isolates. Conclusions: The results demonstrate that the essential oil of R. offi cinalis modulates C. albicans pathogenicity through its primary virulence factor (i.e., germ tube formation was suppressed).